Proposal of a Correlation Model Integrating FDRM and CLSCM Practices and Performance Measures: A Case Study from the Automotive Battery Industry in Brazil - Antonio Marco-Ferreira; Reginaldo Fidelis; Francielle Cristina Fenerich; Rafael Henrique Palma Lima; Pedro Paulo De Andrade Junior; Diogo José Horst (Systems)
The field of closed-loop supply chain management (CLSCM) seeks to replace the linear flow of materials and energy with a cyclical model in which the outputs of the production system become inputs to the same system, thus closing the cycle of materials and energy within the supply chain. Current literature on CLSCM reports a wide variety of practices, and combining these practices with environmental performance measures is an ongoing challenge, mainly because results from these practices are often diffuse and linking them with performance results is not a straightforward task. This paper addresses this problem by proposing a model to prioritize CLSCM practices and performance measures. The correlation model integrating the fuzzy direct rating method (FDRM) and CLSCM practices and performance measures was tested in a real company that is part of a closed-loop supply chain that recycles lead obtained from automotive batteries in Brazil. The results allowed the identification of which management practices are more relevant to the organization by correlating their impact with performance measures. The most relevant practices for the company under study were demand forecasting, with 21.68% of relative importance, followed by reverse logistics practices (21.15%) and production planning and control (18.16%). Another relevant finding is that upstream performance measures account for 77.72% of the company’s CLSCM performance.